2021
DOI: 10.1111/cpr.13119
|View full text |Cite
|
Sign up to set email alerts
|

HDAC8 drives spindle organization during meiotic maturation of porcine oocytes

Abstract: Objectives Histone deacetylase 8 (HDAC8) is one of the class I HDAC family proteins, which participates in the neuronal disorders, parasitic/viral infections, tumorigenesis and many other biological processes. However, its potential function during female germ cell development has not yet been fully understood. Materials and methods HDAC8‐targeting siRNA was microinjected into GV oocytes to deplete HDAC8. PCI‐34051 was used to inhibit the enzyme activity of HDAC8. Immunostaining, immunoblotting and fluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…ACY-241 increased the acetylation of α-tubulin and PCI-34051 increased the acetylation of SMC3. PCI-34051 did not cause detectable α-tubulin acetylation when treated alone, as demonstrated in various studies [ 31 , 41 ]. However, combination treatment of ACY-241 and PCI-34051 significantly increased α-tubulin acetylation, suggesting a cooperative role of PCI-34051 in acetylating α-tubulin when treated along with ACY-241.…”
Section: Resultssupporting
confidence: 62%
“…ACY-241 increased the acetylation of α-tubulin and PCI-34051 increased the acetylation of SMC3. PCI-34051 did not cause detectable α-tubulin acetylation when treated alone, as demonstrated in various studies [ 31 , 41 ]. However, combination treatment of ACY-241 and PCI-34051 significantly increased α-tubulin acetylation, suggesting a cooperative role of PCI-34051 in acetylating α-tubulin when treated along with ACY-241.…”
Section: Resultssupporting
confidence: 62%
“…In addition, histone deacetylases HDAC8 and HDAC6 have been recently proved to negatively regulate α-tubulin acetylation in mouse oocytes. 47,48 In logic consistence, we found that HDAC6 selective inhibitor tubacin can pronouncedly reverse spindle defects induced by paxillin reduction in SLK-depleted oocytes.…”
Section: Discussionmentioning
confidence: 75%
“…In addition, histone deacetylases HDAC8 and HDAC6 have been recently proved to negatively regulate α‐tubulin acetylation in mouse oocytes. 47 , 48 In logic consistence, we found that HDAC6 selective inhibitor tubacin can pronouncedly reverse spindle defects induced by paxillin reduction in SLK‐depleted oocytes. All the evidence supports that SLK facilitates α‐tubulin acetylation by preserving paxillin at a suitable level, thereby ensuring reasonable microtubule stability for the organizing and maintaining a functionally compete for spindle during oocyte meiotic division.…”
Section: Discussionmentioning
confidence: 77%
“…The second observation showed that although the pre-pubertal GV oocytes present improved chromatin organization after FSH treatment, once meiosis is resumed it is usually not completed ( Figures 7D–G ). Previous studies on histone acetylation in oocytes showed that de-acetylation is required for proper meiotic segregation ( Ma and Schultz, 2013 ) ( Sui et al, 2020 ) ( Chen et al, 2021 ). Thus, the acetyl-saturated histone profile of pre-pubertal oocytes treated with FSH pattern might present as an obstacle to their meiotic activity.…”
Section: Discussionmentioning
confidence: 99%